Hepatic Lipidosis in Banded Armadillos (Euphractus sexcinctus) Bred in Captivity - Jael Soares Batista (Acta Scientiae Veterinariae, 2016)
Background: Wild animals bred in captivity may develop steatosis due to unbalanced dietary intake and obesity caused by sedentary behaviour. In some rural areas, six-banded armadillos are raised in captivity inside some metal barrels, with restricted space, and are often overfeed. After getting fattening, armadillos they are slaughtered and used as food. The unfavorable conditions may somehow contribute to likely underlie the development of many diseases, among them we can including hepatic steatosis. The present report aims to describe the pathological findings of hepatic lipidosis in banded armadillos (Euphractus sexcinctus), bred in captivity. Case: The animals were three female adult six-banded armadillos (Euphractus sexcinctus), caught in the native forest of the city of Natal, Rio Grande do Norte, Brazil and raised in domestic environment in a small enclosure and fed with human food leftovers. After eight months kept in these conditions armadillos had severe obesity and then were donated to the city zoo, where they were quarantined and presented clinical symptoms of anorexia for two weeks, weight loss and exhaustion. After being found dead during daily inspection carried out by the veterinarian zoo, the six-banded armadillos were sent to the Animal Pathology Laboratory of Federal Rural University of the Semi-Arid (UFERSA) for pathological examination. The animals presented with a history of anorexia were extremely obese and the autopsy detected had extensive deposits of fat in the carcass and liver. Histopathologically, the liver cells hepatocytes showed marked intracytoplasmic vacuolization and with peripheral displacement of the nucleus to the periphery, with and positive staining for lipids using scarlet Sudan III. To our knowledge, this is the first report of hepatic lipidosis in banded. Discussion: Hepatic lipidosis can be categorized into normal liver and mild, moderate, or severe fatty liver. In severe cases, it is estimated that 80% of the hepatocytes are affected. Therefore, we classified the hepatic lipidosis of the three studied female six-banded armadillos as severe, since the lipids were deposited diffusely. Based on the severity of the lesions and absence of other findings, we concluded here that hepatic lipidosis contributed to the cause of the six-banded armadillos death. The weight of the animals in this report may be associated with innapropriate enclosure dimensions and a diet based on human food leftovers. Such diet was reportedly composed of rice, beens, spaghetti, and bread, which are food with high levels of carbohydrate. The armadillos of the Euphractus sexcinctus species usually weigh between 3 and 6 kg and hence, the animals of this report showed twice the normal weight. The occurrence of hepatic lipidosis associated with anorexia triggered by a stressful event such as a change of environment and diet armadillos observed in the present study is in agreement with literature data pointing anorexia in obese animals as